1991
DOI: 10.1111/j.1745-4549.1991.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE of ULTRASOUND ON the PROPERTIES of CHYMOSIN and the ULTRASTRUCTURE of ABOMASUM DURING CHYMOSIN EXTRACTION

Abstract: The effects of ultrasound treatment on the properties of chymosin and the ultrastructure of abomasum during chymosin extraction were investigated. U1trasound treatment at 36 Wlcm2 for 80 min did not decrease chymosin activity and its proteolytic activity. However, high intensity ultrasound (157 Wlcm2) and the prolonged exposure to high intensity signifzcantly decreased chymosin activity and its proteolytic activity. Ultrasound treatment changed amino acid composition of chymosin. There were signijcant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…At the same time, Kim and Zayas [] observed that higher‐energy ultrasound exposure inhibits the proteolytic activity of chymosin. Following the authors, the prolonged exposure to high ultrasound intensities could directly inactivate enzyme‐active sites.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Kim and Zayas [] observed that higher‐energy ultrasound exposure inhibits the proteolytic activity of chymosin. Following the authors, the prolonged exposure to high ultrasound intensities could directly inactivate enzyme‐active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Anifantakis and Green [175] experimented by changing solutions four times on the same tissue in four days and reported that most enzymes are extracted in the first 24 h, and the rennet is most stable at a pH value of 5.5. The use of ultrasound resulted in an increase in activity and a yield of chymosin with a significantly shorter extraction time (80 min) [182][183][184]. The crude extract is then activated by lowering the pH to around 2.0 for a certain amount of time.…”
Section: Rennet Production Methodsmentioning
confidence: 99%